Eco-friendly polyvinyl alcohol (PVA)/bamboo charcoal (BC) nanocomposites with superior mechanical and thermal properties - Mousa, M.; Dong, Yu; Davies, I. (2016)
Carbon-based nanofillers, such as carbon nanotubes (CNTs) and graphene sheets are considered as effective nanoreinforcements due to their unique structures and material performance. However, the utilisation of such nanofillers can be hindered owing to a high level of nanotoxicity via human inhalation and high material cost for CNTs, as well as the tendency to form agglomerates of graphene sheets in polymer matrices. Bamboo charcoals (BCs) are ecofriendly and sustainable carbon-based particles, which possess good affinity with polyvinyl alcohol (PVA), one of popular water soluble biopolymers, to achieve excellent properties of PVA/BC nanocomposites. In particular, porous structures of BC particles enable polymeric molecules to easily penetrate with the strong internal bonding. In this study, fully ecofriendly PVA/BC nanocomposite films were successfully fabricated by using a simple solution casting method to achieve the high dispersibility of BCs. With the inclusion of only 3 wt% BCs, tensile modulus and tensile strength of PVA/BC nanocomposite films were enhanced by 70.2 and 71.6%, respectively when compared with those of PVA films. Better thermal stability is manifested for resulting nanocomposite films as opposed to that of pristine PVA, which is evidenced by the maximum increase of 17.8% in the decomposition temperature at the weight loss of 80%. It is anticipated that BCs can compete against conventional carbon-based nanofillers with a great potential to be developed into eco-friendly nanocomposites used for thin-film packaging application.